Long-cycle heat-stable lithium supplement diaphragm, preparation method and application thereof, and lithium ion battery
By using a long-circulation thermally stable lithium-adding separator composed of polymer-based film, thermally stable coating and aminolated lithium-adding coating, the problems of poor thermal stability and poor electrolyte emollient in the prior art are solved, and the battery effect with high capacity, high first-time efficiency and excellent circulation performance is achieved.
Patent Information
- Application Number
- CN202510004532.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing lithium supplement membranes have poor thermal stability, poor electrolyte wetting, low liquid retention coefficient, poor lithium supplement effect, high degree of polarization, and poor circulation performance during circulation.
A long-cycle thermally stable lithium-fuel separator consisting of a polymer-based film, a thermally stable coating and an amino-fueled lithium coating are used. The thermally stable coating consists of ceramic powder, polystyrene butadiene copolymer and sodium carboxymethylcellulose. The amino-fueled lithium-fuel coating consists of a amino-fueled lithium compound, a conductive agent and polyvinylidene fluoride, and is combined together by groove mosaic.
The electrolyte has high degree of infiltration, high liquid retention coefficient, good thermal stability and high tensile strength. At the same time, the coating is not easy to fall off during the charging and discharging of the battery, the interface impedance is low, and the degree of side reaction is low. The battery produced has the effects of high capacity, high first-term efficiency and excellent circulation performance.
Smart Images

Figure CN119786888A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery separators, and specifically relates to a long-cycle thermally stable lithium-supplementing separator and a preparation method, application and lithium-ion battery thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the development of the new energy industry, people's requirements for the energy density of lithium-ion batteries are constantly increasing, and the reversible capacity of the positive electrode material, which is closely linked to the energy density, has begun to be valued by people. The key factor affecting the reversible capacity of the positive electrode material is that during the battery formation process, lithium ions form a SEI film on the surface of the negative electrode material. A part of the lithium ions participate in the reaction, making it impossible for these lithium ions to return to the positive electrode to participate in the cycle again. Because the consumption of these lithium ions is one-time, people began to use the method of adding lithium replenishers to make up for this part of the consumed lithium ions. As a result, various lithium replenishment materials and lithium replenishment methods have been developed.
[0004] The diaphragm lithium replenishment process has become one of the most promising lithium replenishment methods in the lithium-ion battery industry due to its advantages such as simple lithium replenishment process, low requirements for the preparation environment, high safety of lithium replenishment materials, and outstanding lithium replenishment effects. Patent CN111816822A proposes a functional lithium replenishment diaphragm, which is composed of a lithium replenishment layer and a base film layer. The components of the lithium replenishment layer are lithium-containing compounds, polymer substrates, and toughening agents, and the base film layer includes a polymer substrate. However, the composition of the lithium replenishment diaphragm is too simple, and it has the disadvantages of poor compatibility between the lithium replenishment layer and the electrolyte, low utilization efficiency of the lithium replenishment material of the lithium replenishment layer, high interface impedance between the lithium replenishment layer-electrolyte-electrode, and easy pulverization and shedding during the cycle. This will lead to poor capacity utilization, cycle performance, and polarization degree of the manufactured battery, and does not take into account the physical property advantages of conventional ceramic coating diaphragms. Summary of the invention
[0005] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a long-cycle thermally stable lithium-supplementing diaphragm and its preparation method, application and lithium-ion battery. The lithium-supplementing diaphragm provided by the present invention has the characteristics of high electrolyte infiltration, high liquid retention coefficient, good thermal stability and high tensile strength. At the same time, during the battery charging and discharging process, the coating in the lithium-supplementing diaphragm is not easy to fall off, the interface impedance with the electrode contact interface is low, and the degree of side reaction with the electrolyte is low. The battery made of the lithium-supplementing diaphragm can achieve high capacity, high initial efficiency and excellent cycle performance.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, a long-cycle thermally stable lithium-replenishing diaphragm is provided, comprising a polymer base film, a thermally stable coating composited on the surface of the polymer base film, and a lithium-replenishing coating composited on the surface of the thermally stable coating;
[0008] The heat-stable coating is a mixture layer formed by ceramic powder, polystyrene butadiene copolymer (SBR) and sodium carboxymethyl cellulose (CMC); the lithium-replenishing coating is a mixture layer formed by amide lithium-replenishing compound, conductive agent and polyvinylidene fluoride (PVDF).
[0009] In some embodiments of the present invention, a groove is provided on the surface of the thermally stable coating, and the lithium-replenishing coating is compounded with the thermally stable coating by being engaged with the groove.
[0010] In some embodiments of the present invention, the thermally stable coating has a maximum thickness of 1.5 to 2.5 μm, a surface groove depth of 0.5 to 1 μm, and a groove width and a spacing between grooves of 0.5 to 1.5 mm.
[0011] In some embodiments of the present invention, the total thickness of the thermally stable coating and the lithium replenishing coating is 4-5 μm.
[0012] In some embodiments of the present invention, the polymer base film includes but is not limited to any one of polyethylene (PE), polypropylene (PP), thermoplastic polyurethane elastomer (TPU), polyetheretherketone (PEEK), polyethylene terephthalate (PET), poly(m-phenylene isophthalamide) (PMIA), poly(m-phenylene isophthalamide-polyurethane) (PMIA-PU), polystyrene support material (PBO), polyvinylidene fluoride (PVDF), polybenzimidazole (PBI), polyphenylene sulfide (PPS) and polyimide (PI).
[0013] It should be noted that the present invention does not limit the thickness of the polymer base film, and the conventional thickness in the art can be adopted. For example, the thickness of the polymer base film can be 7 to 12 μm, specifically 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, and the like.
[0014] In some embodiments of the present invention, the ceramic powder includes but is not limited to any one of boehmite, aluminum oxide, zirconium dioxide, tin oxide, silicon dioxide, magnesium oxide and beryllium oxide.
[0015] It should be noted that the present invention does not impose any requirements on the particle size of the ceramic powder, and the particle size commonly used in the field of lithium-ion battery separator preparation can be used, such as micrometer level, near nanometer level, etc.
[0016] In some embodiments of the present invention, the conductive agent includes but is not limited to any one or more of SP, carbon nanotubes (CNT), vapor grown carbon fiber (VGCF), ECP, reduced graphene oxide (rGO), acetylene black and Carbon ECP.
[0017] In some embodiments of the present invention, the amino lithium-supplementing compound is obtained by reacting 3-aminopropyltriethoxysilane and a lithium-containing compound, and the lithium-containing compound is a lithium-containing metal oxide or lithium ion salt with a theoretical gram capacity of >170mAh / g; preferably, the lithium-containing compound includes but is not limited to any one or more of Li5FeO4, Li5Fe5O8, Li6CoO4, Li2NiO2, Li2O, Li2O2, Li2C2O4, Li2SO4 and Li2SiO3.
[0018] In some embodiments of the present invention, the mass ratio of the ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose is (22-23): 1.5: 1. At this ratio, the thermally stable coating has excellent performance.
[0019] In some embodiments of the present invention, the mass ratio of the aminated lithium-replenishing compound, the conductive agent and polyvinylidene fluoride is (6.5-8):(0.5-1):(3-1). Under this ratio, the lithium-replenishing coating has excellent performance.
[0020] The second aspect of the present invention provides a method for preparing the above-mentioned long-cycle thermally stable lithium-supplementing diaphragm, comprising:
[0021] Ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose are added to the first solvent and mixed to obtain coating A; coating the coating A on the surface of the polymer base film and drying to obtain a single-layer coated diaphragm;
[0022] Adding an aminated lithium-replenishing compound, a conductive agent and polyvinylidene fluoride into a second solvent and mixing them evenly to obtain a coating B; coating B is coated on the single-layer coated diaphragm and dried to obtain a long-cycle thermally stable lithium-replenishing diaphragm.
[0023] It should be noted that, in order to ensure uniform coating, a deaerator can be used to mix and disperse the mixed solution consisting of the raw materials and the solvent. For example, ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose are added to the first solvent to obtain a mixed solution A, and the mixed solution A is mixed and dispersed in a deaerator for 15 to 25 minutes to obtain coating A, and the speed of the deaerator is 1500 to 2500 rpm / min. For example, an amino lithium supplement compound, a conductive agent and polyvinylidene fluoride are added to the second solvent to obtain a mixed solution B, and the mixed solution B is mixed and dispersed in a deaerator for 15 to 25 minutes, and repeated 2 to 4 times to obtain coating B, and the speed of the deaerator is 1500 to 2500 rpm / min.
[0024] In some embodiments of the present invention, the first solvent is water, and the second solvent is an organic solvent, including any one of N-methylpyrrolidone, chloroform, dichloromethane and petroleum ether, preferably N-methylpyrrolidone.
[0025] It should be noted that the lithium-replenishing compounds selected in the present invention react to water to varying degrees, and will damage the lithium-replenishing materials during the aqueous slurry process, causing the lithium-replenishing materials to be inactivated, thereby affecting the lithium-replenishing effect of the diaphragm. The use of an organic solvent as the second solvent can avoid the inactivation of the lithium-replenishing compounds, ensure the stable adhesion of the coating, and effectively improve the cycle life of the lithium-replenishing diaphragm.
[0026] In some embodiments of the present invention, the mass ratio of the ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose is (22-23):1.5:1.
[0027] In some embodiments of the present invention, the mass ratio of the amidated lithium-supplementing compound, the conductive agent and polyvinylidene fluoride is (6.5-8):(0.5-1):(3-1).
[0028] In some embodiments of the present invention, the preparation method comprises: selecting a coating scraper with grooves to coat coating A on a polymer base film, and then vacuum drying at 40 to 50° C. for 8 to 12 hours to obtain a single-layer coated diaphragm with grooves; preferably, the solid content of coating A is 60% to 75%; preferably, when coating A is coated, the coating rate is 2 to 5 mm / s.
[0029] In some embodiments of the present invention, the preparation method includes: selecting a flat coating scraper to apply coating B on the side with the groove coating, and then vacuum drying at 40-50°C for 4-6 hours to obtain a long-cycle thermally stable lithium-supplementing diaphragm; preferably, the solid content of the coating B is 60%-75%; preferably, when applying the coating B, the coating rate is 2-5 mm / s.
[0030] It should be noted that, in order to improve efficiency, increase accuracy and save costs, a vacuum automatic coating machine can be used to apply coating A and coating B.
[0031] In some embodiments of the present invention, the preparation method of the amino lithium-supplementing compound includes: dispersing the lithium-supplementing compound in methanol, ultrasonicating, adding 3-aminopropyltriethoxysilane, reacting at room temperature for 1.5 to 2.5 hours, centrifuging the product and washing it with methanol, and vacuum drying it at 105 to 115° C. for 10 to 12 hours to obtain the amino lithium-supplementing compound.
[0032] In some embodiments of the present invention, the molar ratio of the lithium supplementing compound to 3-aminopropyltriethoxysilane is 1:1.1-1.3.
[0033] The third aspect of the present invention provides a use of the long-cycle thermally stable lithium-replenishing diaphragm or the long-cycle thermally stable lithium-replenishing diaphragm prepared by the above-mentioned preparation method in a lithium-ion battery.
[0034] A fourth aspect of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrode liquid;
[0035] The diaphragm includes the long-cycle heat-stable lithium-replenishing diaphragm mentioned above or the long-cycle heat-stable lithium-replenishing diaphragm prepared by the above-mentioned preparation method.
[0036] The beneficial effects of the present invention are:
[0037] In order to improve the problems of poor thermal stability of lithium replenishing membrane, poor electrolyte wettability, low liquid retention coefficient, poor lithium replenishing effect, large battery polarization degree after battery is manufactured, poor cycle performance, etc., the present invention provides a long-cycle thermally stable lithium replenishing membrane, which is composed of a polymer base film, an inner thermally stable coating and an outer aminated lithium replenishing coating, the thermally stable coating is composed of SBR, CMC, and ceramic materials, the aminated lithium replenishing coating is composed of an aminated lithium replenishing compound, a conductive agent, and PVDF, and the thermally stable coating and the aminated lithium replenishing coating are composited together by groove embedding. The obtained groove embedded composite coating lithium replenishing membrane will have the characteristics of high electrolyte wettability, high liquid retention coefficient, good thermal stability, and high tensile strength. At the same time, during the battery charging and discharging process, the membrane coating is not easy to fall off, the interface impedance of the contact interface with the pole piece is low, and the degree of side reaction with the electrolyte is low. The battery made of the membrane can achieve the effects of high capacity, high initial efficiency, and excellent cycle performance.
[0038] Specifically, the present invention uses an amide lithium-supplementing coating composed of an amide lithium-supplementing compound, a conductive agent, and PVDF as the outer coating of the lithium-supplementing diaphragm. Amino groups exist on the surface of the lithium-supplementing compound particles after amino functionalization. Since amino groups are highly compatible with polar electrolyte solutions, the degree of infiltration of the coating surface to the electrolyte can be significantly improved, and the electrolyte absorption and liquid retention effect is better, thereby improving the ionic conductivity and making the Li in the lithium-supplementing compound + The removal of lithium is more complete, and the amide lithium-supplementing compounds are all lithium-containing metal oxides or lithium ion salts, Li + The transmission rate and electronic conductivity of the coating are much higher than those of conventional boehmite diaphragm coatings, so it has a smaller electrochemical impedance when used in batteries and the interface impedance of the contact interface with the pole piece is also reduced. The presence of the conductive agent in the coating can effectively reduce the interface impedance of the contact interface with the pole piece. The high conductivity of the conductive agent promotes the migration of lithium ions at the electrode-electrolyte interface during repeated cycles. At the same time, because it has the lamellar and pore structure of carbon-based materials, the composite coating diaphragm can further enhance the absorption and retention effect of the electrolyte. The selection of PVDF, an oil-based auxiliary material, is considered from the perspective of coating processing. The lithium-replenishing compounds selected in the present invention have different degrees of reaction to water. In the process of water homogenization, the lithium-replenishing materials will be damaged and inactivated, thereby affecting the lithium-replenishing effect of the diaphragm. At the same time, PVDF, as an excellent toughening agent and binder, can ensure the stable adhesion of the coating, and is not easy to pulverize and fall off during the cycle, which effectively improves the cycle life of the lithium-replenishing diaphragm.
[0039] The use of a thermally stable coating composed of CMC, SBR, and ceramic materials as the inner coating of the lithium replenishment diaphragm can ensure the thermal stability of the lithium replenishment diaphragm. In the actual application of the diaphragm, as the cycle proceeds, the amino lithium replenishment coating may gradually become thinner. With the existence of the inner thermally stable coating, the thermal stability and mechanical properties of the lithium replenishment diaphragm can be maintained at almost the same level as the initial state during the battery cycle; in addition, the water-based auxiliary material system of CMC and SBR is used because compared with other binders such as PVDF and PMMA, the elastomer SBR has higher flexibility, stronger bonding force and higher heat resistance. CMC has two functional groups, carboxylic acid anions and hydroxyl groups, which can well disperse the ceramic powder evenly in the slurry. Under this system, the coating has higher thermal stability, alleviates the thermal shrinkage of the outer amino lithium replenishment coating, and has good mechanical properties such as tensile resistance, bending, and acupuncture resistance.
[0040] The inner and outer coatings are combined together by groove embedding, which can make the combination of the amino lithium-replenishing coating and the thermally stable coating tighter and stronger. The complementary advantages of the two coatings can be maximized, which has a significant effect in alleviating the thermal shrinkage and cycle shedding of the lithium-replenishing coating under high temperature conditions, and also reduces the Li +The resistance of the transmission between the amide lithium supplement coating and the thermally stable coating is reduced, thereby reducing the Li + Electrochemical polarization during the transmission process improves the battery's capacity and cycle performance.
[0041] The presence of the double-layer composite coating can more fully adsorb trace impurities in the electrolyte such as water, HF, etc., thereby reducing side reactions in the battery system, improving interface stability, and improving the cycle performance of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0043] Figure 1 This is a schematic diagram of the structure of a long-cycle thermally stable lithium-supplementing diaphragm according to an embodiment of the present invention;
[0044] Figure 2 This is a contact angle diagram of the electrolyte of the long-cycle thermally stable lithium-supplementing separator obtained in Example 1 of the present invention;
[0045] Figure 3 This is a 0.1C charge-discharge curve of the LFP made of the long-cycle thermally stable lithium-supplementing diaphragm obtained in Example 1 of the present invention.
[0046] Among them, 1-polymer-based film, 2-thermal stable coating, 3-lithium-replenishing coating. DETAILED DESCRIPTION
[0047] In order to improve the problems of poor thermal stability of lithium replenishing diaphragm, poor electrolyte wettability, low liquid retention coefficient, poor lithium replenishing effect, large degree of battery polarization after battery manufacturing, poor cycle performance, etc., the present invention provides a long-cycle thermally stable lithium replenishing diaphragm and its preparation method and lithium-ion battery.
[0048] like Figure 1 As shown, the long-cycle heat-stable lithium-replenishing diaphragm is composed of a polymer base film 1, an inner heat-stable coating 2 and an outer lithium-replenishing coating 3, the heat-stable coating 2 is composed of SBR, CMC and ceramic powder, the lithium-replenishing coating 3 is composed of an amino lithium-replenishing compound, a conductive agent and PVDF, and a groove is provided on the surface of the heat-stable coating 2, and the lithium-replenishing coating 3 is compounded on the surface of the heat-stable coating 2 by being engaged with the groove.
[0049] The present invention also provides a method for preparing a long-cycle thermally stable lithium-supplementing diaphragm, comprising the following steps:
[0050] 1. Ceramic, SBR and CMC are added to water in a ratio of (22-23):1.5:1 to obtain a mixed solution A, and the obtained mixed solution A is mixed and dispersed in a degassing machine for 15-25 minutes to obtain a water-based coating A. A polymer diaphragm is used as a base film and placed in a vacuum automatic coating machine. A coating scraper with a groove is selected to coat the water-based coating A on the base film, and vacuum dried at 40-50°C for 8-12 hours to obtain a single-layer coated diaphragm with a groove. The solid content of the mixed liquid A is 60% to 75%, the rotation speed of the degassing machine is 1500 to 2500 rpm / min, and the coating rate of the vacuum automatic coating machine is 2 to 5 mm / s; the ceramic is one or more of metal oxide ceramics, including but not limited to boehmite, aluminum oxide, zirconium dioxide, tin oxide, silicon dioxide, magnesium oxide, beryllium oxide, etc.; the polymer diaphragm is one of PE, PP, TPU, PEEK, PET, PMIA, PMIA-PU, PBO, PVDF, PBI, PPS and PI with a thickness of 7 to 12 μm; the highest thickness of the grooved coating is 1.5 to 2.5 μm, the height difference between the lowest and highest points of the scraper groove is 0.5 to 1 μm, and the groove width and the spacing between each groove are 0.5 to 1.5 mm.
[0051] 2. Disperse the lithium-replenishing compound powder in methanol and ultrasonicate for 25 to 35 minutes, then add 3-aminopropyltriethoxysilane, react at room temperature for 1.5 to 2.5 hours, centrifuge the product and wash it with methanol several times, and vacuum dry it at 105 to 115° C. for 10 to 12 hours to obtain powdered N-lithium-replenishing compound particles. The lithium-replenishing compound is a lithium-containing metal oxide or lithium ion salt with a theoretical gram capacity of >170 mAh / g, including but not limited to Li5FeO4, Li5Fe5O8, Li6CoO4, Li2NiO2, Li2O, Li2O2, Li2C2O4, Li2SO4 and Li2SiO3.
[0052] 3. Add N-lithium-supplementing compound, conductive agent and PVDF to NMP in a ratio of (6.5-8):(0.5-1):(3-1) to obtain a mixed solution B, and mix and disperse the obtained mixed solution B in a degassing machine for 15-25 minutes, repeat 2-4 times to obtain an oil-based coating B, and then place the grooved single-layer coated diaphragm in a vacuum automatic coating machine, select a flat-mouth coating scraper to coat the coating B on the side with the grooved coating, and finally vacuum dry at 40-50° C. for 4-6 hours to obtain a groove-embedded composite coating lithium-supplementing diaphragm. The solid content of the mixed solution B is 60%-75%, the rotation speed of the degassing machine is 1500-2500rpm / min, the coating rate of the vacuum automatic coating machine is 2-5mm / s, the conductive agent is one or more of SP, CNT, VGCF, ECP, rGO, acetylene black, and Carbon ECP, and the total thickness of the two layers of coating of the lithium-supplementing diaphragm is 4-5μm.
[0053] The long-cycle heat-stable lithium-supplementing diaphragm prepared by the present invention has the characteristics of high electrolyte infiltration, high liquid retention coefficient, good thermal stability and high tensile strength. At the same time, during the battery charging and discharging process, the diaphragm coating is not easy to fall off, the interface impedance of the contact interface with the electrode is low, and the degree of side reaction with the electrolyte is low. The battery made of the diaphragm can achieve high capacity, high initial efficiency and excellent cycle performance.
[0054] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0055] The raw materials used in the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0056] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials of conventional purity used in the field of lithium ion battery separator preparation.
[0057] Example 1
[0058] A method for preparing a long-cycle thermally stable lithium-supplementing diaphragm comprises the following steps:
[0059] 1. Add boehmite, SBR and CMC to DI water at a mass ratio of 22.5:1.5:1 to obtain a mixed solution A. The solid content of the mixed solution A is controlled to be 65%, and the obtained mixed solution A is mixed and dispersed in a degassing machine at a speed of 1800rpm / min for 17min to obtain a water-based coating A. A PE diaphragm with a thickness of 12μm is used as the base film and placed in a vacuum automatic coating machine. A coating scraper with a groove width and a spacing distance between each groove of 0.5mm and a height difference of 1μm between the lowest and highest points is selected to coat the water-based coating A on the base film at a coating rate of 2mm / s, and vacuum dried at 48°C for 10h to obtain a single-layer coated diaphragm with grooves, and the thickness of the grooved coating at the highest point is 2μm.
[0060] 2. Disperse Li5FeO4 powder in methanol and ultrasonicate for 30 minutes, then add 3-aminopropyltriethoxysilane, the molar ratio of Li5FeO4 to 3-aminopropyltriethoxysilane is 1:1.3, react at room temperature for 2 hours, centrifuge the product and wash it with methanol several times, and vacuum dry it at 110°C for 12 hours to obtain powdered N-Li5FeO4 particles.
[0061] 3. Add N-Li5FeO4, SP, and PVDF to NMP at a mass ratio of 8:1:1 to obtain a mixed solution B. The solid content of the mixed solution B is controlled to be 65%, and the obtained mixed solution B is mixed and dispersed in a degassing machine at a speed of 2000rpm / min for 17min, and repeated 3 times to obtain an oil-based coating B. Then place the single-layer coated diaphragm with grooves obtained in step 1 in a vacuum automatic coating machine, select a flat-mouth coating scraper to apply the oil-based coating B on the side with the groove coating at a coating rate of 2mm / s, and finally vacuum dry at 50°C for 6h to obtain a groove-embedded composite coating lithium-replenishing diaphragm, that is, a long-cycle thermally stable lithium-replenishing diaphragm, and the total thickness of the two layers of coating applied on the base film is 4.5μm.
[0062] Example 2
[0063] A method for preparing a long-cycle thermally stable lithium-supplementing diaphragm, which differs from Example 1 in that the lithium-supplementing compound in step 2 is Li2C2O4, and the remaining steps are consistent with Example 1.
[0064] Example 3
[0065] A method for preparing a long-cycle thermally stable lithium-replenishing diaphragm, which differs from Example 1 in that the highest thickness of the grooved coating in step 1 is 1.5 μm, the total thickness of the two coating layers in step 3 is 5 μm, and the remaining steps are consistent with Example 1.
[0066] Example 4
[0067] A method for preparing a long-cycle thermally stable lithium-replenishing diaphragm, which differs from Example 1 in that the highest thickness of the grooved coating in step 1 is 2.5 μm, the total thickness of the two coating layers in step 3 is 4 μm, and the remaining steps are consistent with Example 1.
[0068] Comparative Example 1
[0069] A method for preparing a lithium supplementing diaphragm comprises the following steps:
[0070] 1. Add boehmite, SBR and CMC to DI water at a mass ratio of 22.5:1.5:1 to obtain a mixed solution. The solid content of the mixed solution is controlled to be 65%, and the obtained mixed solution is mixed and dispersed in a degassing machine at a speed of 1800rpm / min for 17min to obtain a water-based coating. A PE diaphragm with a thickness of 12μm is used as the base film and placed in a vacuum automatic coating machine. A flat coating scraper is selected to coat the water-based coating on the base film at a coating rate of 2mm / s, and vacuum dried at 48°C for 10h to obtain a ceramic single-layer coated diaphragm with a coating thickness of 4.5μm.
[0071] Comparative Example 2
[0072] A method for preparing a lithium supplementing diaphragm comprises the following steps:
[0073] Li5FeO4 and PVDF were added to NMP at a mass ratio of 8.5:1.5 to obtain a mixed solution. The solid content of the mixed solution was controlled to be 65%, and the obtained mixed solution was mixed and dispersed in a degassing machine at a speed of 2000rpm / min for 17min, and repeated 3 times to obtain an oil-based coating. A PE diaphragm with a thickness of 12μm was used as the base film and placed in a vacuum automatic coating machine. A flat-mouth coating scraper was selected to coat the oil-based coating on the base film at a coating rate of 2mm / s, and finally vacuum dried at 50℃ for 6h to obtain a lithium-supplementing coating diaphragm with a coating thickness of 4.5μm.
[0074] Comparative Example 3
[0075] A method for preparing a lithium supplementing diaphragm comprises the following steps:
[0076] 1. Boehmite, SBR and CMC were added to DI water at a mass ratio of 22.5:1.5:1 to obtain a mixed solution A. The solid content of the mixed solution A was controlled to be 65%, and the obtained mixed solution A was mixed and dispersed in a degassing machine at a speed of 1800 rpm / min for 17 minutes to obtain a water-based coating A. A PE diaphragm with a thickness of 12 μm was used as a base film and placed in a vacuum automatic coating machine. A flat coating scraper was selected to coat the coating A on the base film at a coating rate of 2 mm / s, and vacuum dried at 48°C for 10 hours to obtain a single-layer coated diaphragm with a coating thickness of 2 μm.
[0077] Step 2 and step 3 are consistent with those of Example 1.
[0078] Comparative Example 4
[0079] A method for preparing a lithium supplementing diaphragm comprises the following steps:
[0080] 1. Add boehmite, SBR and CMC to DI water at a mass ratio of 22.5:1.5:1 to obtain a mixed solution A. The solid content of the mixed solution A is controlled to be 65%, and the obtained mixed solution A is mixed and dispersed in a degassing machine at a speed of 1800 rpm / min for 17 minutes to obtain a water-based coating A. A PE diaphragm with a thickness of 12 μm is used as a base film and placed in a vacuum automatic coating machine. A coating scraper with a groove width and a spacing distance between each groove of 0.5 mm and a height difference of 1 μm between the lowest and highest points is selected to coat the water-based coating A on the base film at a coating rate of 2 mm / s, and vacuum dried at 48°C for 10 hours to obtain a single-layer coated diaphragm with grooves, and the thickness of the highest point of the grooved coating is 2 μm.
[0081] 2. Li5FeO4 and PVDF were added to NMP at a mass ratio of 8.5:1.5 to obtain a mixed solution B. The solid content of the mixed solution B was controlled to be 65%, and the obtained mixed solution B was mixed and dispersed in a degassing machine at a speed of 2000rpm / min for 17min, and repeated 3 times to obtain an oil-based coating B. The single-layer coated diaphragm with grooves obtained in step 1 was placed in a vacuum automatic coating machine, and a flat-mouth coating scraper was selected to coat the oil-based coating B on the side with the groove coating at a coating rate of 2mm / s. Finally, it was vacuum dried at 50°C for 6h to obtain a groove-embedded composite coating lithium-supplementing diaphragm, and the total thickness of the two layers of coating coated on the base film was 4.5μm.
[0082] Performance Testing
[0083] Thermal shrinkage test: Cut 3 samples of 10cm×10cm, draw cross lines along the longitudinal shrinkage (MD) and transverse shrinkage (TD) directions, and mark the MD and TD directions. Place the sample between A4 papers (1 each on the top and bottom). After heating for 1 hour at the set temperature, measure the length of the cross lines to calculate the shrinkage. Shrinkage % = (L0-L1) / L0*100% (L0: initial sample cross line length, L1: cross line measurement length after heating). The average value of the 3 points is taken as the thermal shrinkage of the sample.
[0084] Tensile strength test: Cut the sample: 200mm×10mm, no burrs or tears on the edge, the thickness value is the actual test average value, the chuck spacing: 100mm, the speed: 200mm / min, and the result is the average value of 3 points. (GB / T1040.3-2006)
[0085] Preparation of button cells: Add conductive carbon black to the polyvinylidene fluoride NMP solution, then add lithium iron phosphate powder, stir evenly, and evenly apply the slurry on the aluminum foil on the coater to make a pole piece. Put the coated pole piece into a vacuum drying oven at a temperature of 120°C and vacuum dry it for 6 hours. Take out the pole piece and roll it on a roller press for use. The button cell is assembled in a glove box under an argon atmosphere. The electrolyte is 1M LiPF6+EC:DEC:DMC=1:1:1 (volume ratio). The metal lithium sheet is the counter electrode, and the diaphragm is the diaphragm made in the embodiment or comparative example of the present invention. The capacity test is carried out on an American ArbinBT2000 battery tester. The charge and discharge voltage range is 2 to 4.2V, and the charge and discharge rates are 0.1C and 1C, respectively.
[0086] The test results are shown in Tables 1 and 2.
[0087] Table 1 Comparison of physical properties of the diaphragms obtained in the examples and comparative examples
[0088]
[0089] As can be seen from Table 1, the contact angle and tensile strength of the lithium-supplementing diaphragm prepared in the embodiment are slightly lower than those of the lithium-supplementing diaphragm prepared in Comparative Example 1, and the thermal shrinkage rate is slightly higher, but there is no obvious difference in the overall physical parameters. Compared with Comparative Example 2, Example 1 shows that because the lithium-supplementing layer in the lithium-supplementing diaphragm prepared in Example 1 has undergone an amino functionalization reaction, the degree of wettability of the coating surface to the electrolyte is significantly improved, and the contact angle is greatly reduced. At the same time, due to the presence of the inner thermally stable coating and the groove interlocking coating scheme, the thermal stability and mechanical properties of the diaphragm are better, so the tensile strength is significantly higher and the thermal shrinkage rate is significantly lower. Compared with Comparative Example 3, Example 1 shows that because Comparative Example 3 does not adopt the groove interlocking coating scheme, the tensile strength of the comparative example is reduced, and the thermal shrinkage rate is also increased to a certain extent. Compared with Comparative Example 4, Example 1 has an additional amino functionalization step, so the degree of wettability of the coating surface to the electrolyte is significantly improved, so the contact angle of Example 1 is significantly reduced.
[0090] Table 2 Electrical properties of LFP buckle made of diaphragm of embodiment and comparative example
[0091]
[0092] As shown in Table 2, compared with the buckle battery of Comparative Example 1, the 0.1C charging capacity of the buckle battery made of the embodiment diaphragm has been improved by about 10 mAh / g, and the first efficiency has been greatly reduced, which shows that the lithium supplement component has been charged to the negative electrode to form a film or storage, and the lithium supplement effect has been effectively played. At the same time, the 1C first cycle discharge capacity and the capacity retention rate after 1C 50 cycles have been greatly improved. Compared with Comparative Example 2, because the lithium supplement coating has been amino-functionalized and a conductive agent has been added, the Li +The release is more complete and the transmission rate is faster, so the 0.1C charging capacity is higher and the first efficiency is lower. At the same time, because the coating has a smaller electrochemical impedance and the interface impedance of the contact interface with the electrode is lower, as well as the synergistic effect of the groove-embedded composite coating, the 1C first-cycle specific capacity and the capacity retention rate after 1C50 cycles are also higher, and the cycle performance is better. Compared with Comparative Example 3, the embodiment lacks the groove-embedded coating solution, so there is a significant difference in cycle performance. The capacity retention rate of the embodiment after 1C50 cycles is higher, and the 1C first-cycle specific capacity is also slightly higher. Compared with Comparative Example 4, the embodiment lacks the amino functionalization of the lithium-supplementing coating and the addition of a conductive agent, so the 0.1C charging capacity of the embodiment is significantly higher and the first efficiency is lower. At the same time, the 1C first-cycle discharge capacity and the capacity retention rate after 1C50 cycles are also higher, and the comprehensive electrical performance is better. Comparative Examples 3, 4 and all the embodiments use a composite coating, so there are fewer side reactions in the system during the cycle and the interface stability is higher. Therefore, compared with Comparative Examples 1 and 2, the capacity retention rate after 1C50 cycles is higher and the cycle performance is better.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A long-cycle thermally stable lithium-supplementing diaphragm, characterized in that: It includes a polymer base film, a heat-stable coating compounded on the surface of the polymer base film, and a lithium-replenishing coating compounded on the surface of the heat-stable coating; The thermally stable coating is a mixture layer formed by ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose; the lithium supplement coating is a mixture layer formed by an amino lithium supplement compound, a conductive agent and polyvinylidene fluoride.
2. The long-cycle thermally stable lithium-supplementing diaphragm according to claim 1, characterized in that: The surface of the thermally stable coating is provided with a groove, and the lithium-replenishing coating is compounded with the thermally stable coating by being embedded in the groove.
3. The long-cycle thermally stable lithium-supplementing diaphragm according to claim 1, characterized in that: The thickness of the thermally stable coating at the highest point is 1.5 to 2.5 μm, the depth of the surface grooves is 0.5 to 1 μm, and the width of the grooves and the spacing between the grooves are both 0.5 to 1.5 mm; Preferably, the total thickness of the thermally stable coating and the lithium replenishing coating is 4-5 μm.
4. The long-cycle thermally stable lithium-supplementing diaphragm according to claim 1, characterized in that: The polymer base film includes any one of polyethylene, polypropylene, thermoplastic polyurethane elastomer, polyetheretherketone, polyethylene terephthalate, poly(m-phenylene isophthalamide), poly(m-phenylene isophthalamide-polyurethane), polystyrene support rod material, polyvinylidene fluoride, polybenzimidazole, polyphenylene sulfide and polyimide; Preferably, the ceramic powder includes any one of boehmite, aluminum oxide, zirconium dioxide, tin oxide, silicon dioxide, magnesium oxide and beryllium oxide; Preferably, the conductive agent includes any one or more of SP, carbon nanotubes, vapor-grown carbon fibers, ECP, reduced graphene oxide, acetylene black and Carbon ECP; Preferably, the amino lithium-supplementing compound is obtained by reacting 3-aminopropyltriethoxysilane and a lithium-containing compound, and the lithium-containing compound is a lithium-containing metal oxide or lithium ion salt with a theoretical gram capacity of >170 mAh / g; preferably, the lithium-containing compound includes any one or more of Li5FeO4, Li5Fe5O8, Li6CoO4, Li2NiO2, Li2O, Li2O2, Li2C2O4, Li2SO4 and Li2SiO3.
5. The long-cycle thermally stable lithium-supplementing diaphragm according to claim 1, characterized in that: The mass ratio of the ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose is (22-23):1.5:1; Preferably, the mass ratio of the aminated lithium-supplementing compound, the conductive agent and polyvinylidene fluoride is (6.5-8):(0.5-1):(3-1).
6. A method for preparing the long-cycle thermally stable lithium-supplementing diaphragm according to claim 1, characterized in that: include: Ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose are added to the first solvent and mixed to obtain coating A; coating the coating A on the surface of the polymer base film and drying to obtain a single-layer coated diaphragm; Adding an aminated lithium-replenishing compound, a conductive agent and polyvinylidene fluoride into a second solvent and mixing them evenly to obtain a coating B; coating B is coated on the single-layer coated diaphragm and dried to obtain a long-cycle thermally stable lithium-replenishing diaphragm.
7. The preparation method according to claim 6, characterized in that: The first solvent is water, and the second solvent is an organic solvent, including any one of N-methylpyrrolidone, chloroform, dichloromethane and petroleum ether, preferably N-methylpyrrolidone; Preferably, the mass ratio of the ceramic powder, polystyrene butadiene copolymer and sodium carboxymethyl cellulose is (22-23):1.5:1; Preferably, the mass ratio of the lithium-supplementing compound, the conductive agent and polyvinylidene fluoride is (6.5-8):(0.5-1):(3-1); Preferably, the preparation method comprises: selecting a coating scraper with grooves to coat coating A on a polymer base film, and then vacuum drying at 40 to 50° C. for 8 to 12 hours to obtain a single-layer coated diaphragm with grooves; preferably, the solid content of coating A is 60% to 75%; preferably, when coating coating A is coated, the coating rate is 2 to 5 mm / s; Preferably, the preparation method comprises: selecting a flat coating scraper to apply coating B on the side with the groove coating, and then vacuum drying at 40 to 50° C. for 4 to 6 hours to obtain a long-cycle thermally stable lithium-supplementing diaphragm; preferably, the solid content of coating B is 60% to 75%; preferably, when applying coating B, the coating rate is 2 to 5 mm / s.
8. The preparation method according to claim 6, characterized in that: The preparation method of the aminated lithium-supplementing compound comprises: dispersing the lithium-supplementing compound in methanol, ultrasonicating, adding 3-aminopropyltriethoxysilane, reacting at room temperature for 1.5 to 2.5 hours, centrifuging the product and washing it with methanol, and vacuum drying it at 105 to 115° C. for 10 to 12 hours to obtain the aminated lithium-supplementing compound; Preferably, the molar ratio of the lithium supplement compound to 3-aminopropyltriethoxysilane is 1:1.1-1.
3.
9. Use of the long-cycle heat-stable lithium-supplementing diaphragm according to any one of claims 1 to 5 or the long-cycle heat-stable lithium-supplementing diaphragm prepared by the preparation method according to any one of claims 6 to 9 in a lithium-ion battery.
10. A lithium ion battery, characterized in that: Including positive electrode, negative electrode, separator and electrode liquid; The diaphragm includes the long-cycle heat-stable lithium-replenishing diaphragm described in any one of claims 1-5 or the long-cycle heat-stable lithium-replenishing diaphragm prepared by the preparation method described in any one of claims 6-9.
Citation Information
Patent Citations
Functionalized lithium supplementing diaphragm and preparation method thereof
CN111816822A
Porous functional coating diaphragm, preparation method thereof and lithium ion battery
CN116780097A
Lithium supplement agent and preparation method thereof, diaphragm and preparation method thereof, and battery
CN116813499A
Cited By
Separator and electrochemical device
CN121663112A